Presence of "One Pill Can Kill" Medications in Medication Organizers: Implications for Child Safety. (December 2022) - Farrell, Natalija M.; Hamilton, Sebastian; Gendron, Bryan J.; Corio, Jessica L.; Lookabill, Sara K.
Background: Medication organizers increased compliance, but they do not contain child protective packaging. Medications organizers have been involved in some pediatric exposures; however, previous reports do not describe if "one pill can kill" (1PCK) medications were involved in the exposures. 1PCK medications may cause toxicity even with a single tablet. Objective: The purpose of this study is to describe the type and presence of 1PCK medications dispensed in medication organizers at a single center. Methods: Adult patients who received blister packed medications from September 1, 2017 to September 30, 2017 were included in this retrospective review. Medications were excluded if dispensed traditionally during this time. The primary outcome described included 1PCK medications (quantity and type). Secondary outcomes included total number of tablets dispensed, delayed- (DR) and extended-release (ER) formulations, average age of those dispensed 1PCK medications versus those without. Results: A total of 450 patients received 486 blister packs and 75.5% of which found to include 1PCK medications. Most commonly included 1PCK medications were beta-blockers and calcium channel blockers (42.4 and 49.4%, respectively). Patients receiving 1PCK medications were older (69.1 ± 12.6 vs 62.6 ± 16.7 years old, p < 0.0001) and included more medications (8.5 ± 2.9 vs 5.7 ± 2.9 medications, p < 0.0001). DR and ER formulations were in 150 packs. Conclusion: The majority of dispensed medication organizers included 1PCK medications. Upon dispensing, patients should be questioned for possible proximity exposures. Additionally, they should receive education on medication safety for children that may be in proximity of the medications during home, work, or social activities.